Catalyst for synthesizing biomass propylene as well as preparation method and application of catalyst

By using the Al-Beta@Si-Beta catalyst modified with composite oxide, the problems of low propylene yield and poor catalyst stability in the prior art are solved, high propylene yield and excellent hydrothermal stability are achieved, and the economic and efficiency of the catalytic process is improved.

CN119657213AActive Publication Date: 2025-03-21CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202311227512.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-21
Publication Date
2025-03-21
Estimated Expiration
2043-09-21

AI Technical Summary

Technical Problem

In the prior art, when catalyzing the preparation of low-carbon olefins of bioethanol, the yield of propylene is not high and the hydrothermal stability of the catalyst is poor.

Method used

The Al-Beta@Si-Beta catalyst modified with composite oxide was prepared by impregnation method, and the core-shell structure of the Al-Beta@Si-Beta composite molecular sieve was used to inhibit the activity of non-selective acidic sites on the outer surface and keep the pores unobstructed, thereby improving the selectivity and yield of propylene and improving the hydrothermal stability of the catalyst.

Benefits of technology

The yield of propylene and the hydrothermal stability of the catalyst are significantly improved, the occurrence of side reactions is inhibited, and the selectivity and economicality of the catalyst are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119657213A_ABST
    Figure CN119657213A_ABST
Patent Text Reader

Abstract

The invention provides a catalyst for synthesizing biomass propylene as well as a preparation method and application of the catalyst. The catalyst comprises: a) 1-20 parts of at least one selected from oxides of Zn, In, Ga, W and Mo; b) 0.5-10 parts of at least one of oxides of P and rare earth elements; c) 30 to 98.5 parts of an Al-Beta (at) Si-Beta composite molecular sieve; and d) 0-68 parts of a matrix. The catalyst is used in a reaction for synthesizing biomass propylene, and has the beneficial effects of high propylene yield and excellent hydrothermal stability of the catalyst.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of bio-propylene catalysts, and in particular relates to a catalyst for synthesizing biomass propylene, a preparation method and an application thereof. Background Art

[0002] Propylene is one of the important organic chemical raw materials and is widely used in the preparation of chemicals such as propylene oxide, acrylonitrile, polypropylene and polyether. At present, propylene mainly comes from steam cracking and catalytic cracking processes. In essence, the above propylene preparation processes are still part of the process of preparing low-carbon olefins using fossil energy as raw materials. However, the processing of fossil energy is accompanied by a large amount of CO 2 emissions, which is the main cause of global warming. Global warming has led to frequent extreme weather events, which has attracted widespread attention from countries around the world. How to reduce the use of fossil energy and reduce CO 2 Emissions are an important issue that must be faced in the current global economic development process.

[0003] In recent years, with the rapid development of biochemical technology, the technology of producing ethanol from biomass (such as lignin and cellulose) has made important progress. The carbon emissions from biomass are almost zero. Therefore, the process of producing biomass propylene using bioethanol as raw material is very important to reduce the CO2 emissions from the existing propylene production process. 2 Emissions and ensuring national energy security are of great practical significance.

[0004] CN105148897A discloses a catalyst for catalyzing bioethanol to prepare low-carbon olefins, and its preparation method and application. The method comprises the following steps: mixing a zirconium source and a yttrium source, and then dropping a precipitant to co-precipitate the zirconium source and the yttrium source, and drying and calcining the precipitate to obtain ZrO 2 / Y 2 O 3 The catalyst can be used in the catalytic conversion of ethanol to propylene, showing good selectivity and stability, with a propylene yield of about 44.0% and an ethylene yield of about 31.3%. The catalyst prepared by this method has the problem of low selectivity and yield of propylene in the reaction.

[0005] CN112958066A discloses a catalyst for preparing low-carbon olefins from bioethanol and its application. The method synthesizes a Ga-doped zirconium-based composite metal oxide (ZrO 2 / Ga 2 O 3) catalyst, used for catalytic conversion of ethanol to light olefins, the yield of ethylene is about 2.5%, the yield of propylene is about 29.8%, and the best yield of isobutylene is about 40.0%. The process still has the problem of low propylene yield, and no data on the hydrothermal stability of the catalyst is provided.

[0006] In summary, the existing technologies have problems of low propylene yield and poor catalyst stability to varying degrees. Summary of the invention

[0007] In view of the defects of the prior art, the present invention provides a novel catalyst for synthesizing biomass propylene and its preparation method and application. The catalyst is used in the reaction of synthesizing biomass propylene and has the beneficial effects of high propylene yield and excellent hydrothermal stability of the catalyst.

[0008] The first aspect of the present invention provides a catalyst for synthesizing biomass propylene, which comprises, by weight:

[0009] a) 1 to 20 parts of at least one oxide selected from Zn, In, Ga, W, and Mo;

[0010] b) 0.5 to 10 parts of at least one selected from P and oxides of rare earth elements;

[0011] c) 30 to 98.5 parts of Al-Beta@Si-Beta composite molecular sieve;

[0012] d) 0 to 68 parts of matrix.

[0013] According to the present invention, preferably, component a) is 4 to 12 parts of at least one oxide selected from Zn, In, Ga, W, and Mo.

[0014] According to the present invention, preferably, component b) is 1.5 to 7.5 parts of at least one selected from P and oxides of rare earth elements.

[0015] According to the present invention, the matrix in component d) is at least one of silicon oxide, aluminum oxide, zirconium oxide, titanium oxide and clay. The clay includes at least one of kaolin, bentonite, diatomaceous earth, attapulgite and white clay.

[0016] According to the present invention, the Al-Beta@Si-Beta composite molecular sieve in component c) is a core-shell composite molecular sieve with Al-Beta as the core phase and Si-Beta as the shell phase. The core-shell weight ratio is 70-99:1-30. Among them, Si-Beta is an all-silicon Beta molecular sieve. Al-Beta is an aluminum-containing Beta molecular sieve. The silicon-aluminum molar ratio of Al-Beta molecular sieve is SiO 2 / Al 2 O3 It ranges from 10 to 400.

[0017] According to the present invention, the Al-Beta@Si-Beta composite molecular sieve has a specific surface area of ​​580 to 720 m 2 / g, and the external surface activity index is less than or equal to 10%, preferably 0.01% to 10%, and further less than or equal to 5%.

[0018] The second aspect of the present invention provides a method for preparing the above catalyst. The catalyst is prepared by an impregnation method, specifically, the Al-Beta@Si-Beta composite molecular sieve is impregnated with an impregnation solution containing a component a) source, a component b) source, and optionally a component d) source, and the catalyst is obtained by aging and calcining.

[0019] According to the present invention, the source of a) is a salt containing component a), preferably a nitrate.

[0020] According to the present invention, the source of b) is a salt containing component b), preferably a nitrate.

[0021] According to the present invention, the aging time is 2 to 48 hours, and the aging temperature is 10 to 35°C.

[0022] According to the present invention, the calcination time is 1 to 72 hours, and the calcination temperature is 500 to 700° C. Preferably, drying can be performed before calcination, and the drying temperature is 60 to 200° C. and the drying time is 2 to 48 hours.

[0023] According to the present invention, the preparation method of the Al-Beta@Si-Beta composite molecular sieve comprises:

[0024] 1) mixing a silicon source, a template R and water, and aging the mixture to obtain a mixture I;

[0025] 2) taking a portion of the mixture I and subjecting it to hydrothermal crystallization to obtain a mixture II;

[0026] 3) impregnating Al-Beta molecular sieve with an impregnation solution containing mixture II, and obtaining precursor III after aging and first calcination;

[0027] 4) Another part of the mixture I is hydrothermally crystallized with the precursor III and then calcined for the second time to obtain the Al-Beta@Si-Beta composite molecular sieve.

[0028] According to the present invention, in the preparation method of the Al-Beta@Si-Beta composite molecular sieve, the feeding ratio of the silicon source, the template R and the water in step 1) is SiO 2 :R:H 2O=10:1-10:100-1000, in moles. The silicon source includes at least one of white carbon black, silica sol, silica gel and organic silicone grease. The template includes at least one of tetraethylammonium hydroxide and tetraethylammonium bromide.

[0029] According to the present invention, in the preparation method of the Al-Beta@Si-Beta composite molecular sieve, the aging temperature in step 1) is 10 to 50° C., and the aging time is 24 to 96 hours.

[0030] According to the present invention, in the preparation method of the Al-Beta@Si-Beta composite molecular sieve, the temperature of the hydrothermal crystallization in step 2) is 80-150° C., and the crystallization time is 24-196 hours. The mixture II is transparent or translucent.

[0031] According to the present invention, in the preparation method of the Al-Beta@Si-Beta composite molecular sieve, in step 3), Al-Beta is a conventional Beta molecular sieve. The silicon-aluminum molar ratio of the Al-Beta molecular sieve is SiO 2 / Al 2 O 3 It ranges from 10 to 400.

[0032] According to the present invention, in the preparation method of the Al-Beta@Si-Beta composite molecular sieve, in step 3), the impregnation solution containing the mixture II contains SiO 2 The mass ratio of the impregnation material to the Al-Beta molecular sieve is 1:100 to 10:100. As a preferred embodiment, the impregnation is directly followed by aging and first calcination without filtering or washing.

[0033] According to the present invention, in the preparation method of the Al-Beta@Si-Beta composite molecular sieve, the aging temperature in step 3) is no more than 35°C, preferably 10-35°C, and the aging time is 1-48h. The temperature of the first roasting is 500-650°C, and the roasting time is 1-48h. Drying can also be performed before roasting, the drying temperature is 60-200°C, and the drying time is 2-48h.

[0034] According to the present invention, in the preparation method of the Al-Beta@Si-Beta composite molecular sieve, in the crystallization raw material of step 4), the liquid-to-solid ratio is 2:1 to 20:1 by weight. As a non-limiting example, the liquid-to-solid ratio can be any value of 3:1, 5:1, 8:1, 10:1, 12:1, 15:1, 17:1, etc.

[0035] According to the present invention, in the preparation method of the Al-Beta@Si-Beta composite molecular sieve, the crystallization equipment in step 4) is preferably a crystallization kettle. The crystallization conditions are: crystallization at 100-180° C. for 24-96 hours.

[0036] According to the present invention, in the preparation method of the Al-Beta@Si-Beta composite molecular sieve, the second calcination conditions in step 4) are: temperature 500-650°C and time 1-48h. Washing and drying can be performed before calcination. The drying conditions are: temperature 60-200°C and time 2-72h.

[0037] The third aspect of the present invention provides use of the above catalyst or the catalyst prepared by the above preparation method in the reaction of preparing biomass propylene.

[0038] According to the present invention, in the application, biomass ethanol is used as raw material, wherein the weight content of ethanol is 10-100%, preferably 30%-100%.

[0039] According to the present invention, in the application, the ethanol-containing material is contacted with the catalyst to react to obtain a propylene-containing stream.

[0040] According to the present invention, the reaction conditions are: the absolute reaction pressure is 0.1-2.0 MPa, the ethanol feed weight space velocity is 0.5-10 h -1 , the reaction temperature is 400-600℃.

[0041] According to the present invention, preferably, the reaction conditions are: the absolute reaction pressure is 0.1-0.8 MPa, the ethanol feed weight space velocity is 1.0-4 h -1 , reaction temperature 430~550℃.

[0042] Compared with the prior art, the present invention has the following advantages:

[0043] (1) The reaction pathway for ethanol to propylene is very complex. When propylene is produced, CO is also produced. 2 , methane, ethylene, C4 and other by-products. How to suppress the formation of side reactions and improve the relative selectivity of propylene in the product is an important way to improve the economy of the process. In the catalyst of the present invention, Al-Beta@Si-Beta modified with a composite oxide is used as a catalyst, which reduces the acidity of the outer surface of the catalyst, suppresses the activity of the non-selective acidic sites on the outer surface, and at the same time maintains the patency of the pores, suppresses the occurrence of selective side reactions such as polymerization and carbon deposition on the outer surface, thereby improving the selectivity and yield of the catalyst for propylene.

[0044] (2) In the catalyst preparation method of the present invention, the Al-Beta molecular sieve is covered with a crystallized precursor species, and then a secondary crystallization is performed, so that Si-Beta can be more evenly covered on the surface of the Al-Beta molecular sieve, covering the acidity of the outer surface of the Al-Beta molecular sieve, which is beneficial to suppressing the occurrence of non-selective polymerization and carbon deposition side reactions on the outer surface.

[0045] (3) In the application of the present invention, the Al-Beta@Si-Beta modified with the novel composite oxide of the present invention is used as a catalyst for the reaction of ethanol to propylene, which has the advantage of high propylene yield. BRIEF DESCRIPTION OF THE DRAWINGS

[0046] Figure 1 This is the XRD diagram of Al-Beta@Si-Beta and Al-Beta in Example 1. DETAILED DESCRIPTION

[0047] The present invention will be further described below by way of examples, but the protection scope of the present invention is not limited by the examples.

[0048] In the present invention, XRD is tested by Rigaku D / MAX-1400X polycrystalline X-ray diffractometer, and the test conditions are: graphite monochromator, Cu K ray, tube voltage 40kV, tube current 40mA, and scanning speed 15° / min.

[0049] In the present invention, the silicon-aluminum ratio is measured by XRF spectroscopy, the testing equipment is: Philips Magix X-ray fluorescence spectrometer, the testing conditions are: Rhodium X-ray tube, tube voltage 60kV, tube current 40mA.

[0050] In the present invention, the specific surface area of ​​the sample is N 2 The physical adsorption test and analysis were carried out on a Micromeritics TriStar3000 multi-channel physical adsorption instrument at an operating temperature of -196°C.

[0051] In the present invention, the external surface activity index of the sample is used to characterize the catalytic activity of the non-selective acidic sites on the external surface of the catalyst. The higher the activity index, the higher the degree of non-selective side reactions. The external surface activity index of the sample is characterized by the ratio of the conversion activity of the sample to be tested to the benchmark Beta molecular sieve catalyst for triisopropylbenzene. The benchmark catalyst adopts the commercial Beta molecular sieve (silicon aluminum molar ratio SiO 2 / Al 2 O 3=25, product model NKF-6-25H). Evaluation steps and conditions: crush the sample tablets to 20-40 mesh; catalyst loading 2.0g, reaction temperature 480℃, reaction pressure normal pressure, triisopropylbenzene WHSV=1.05h -1 , N 2 The partial pressure was 50%. The reaction products were analyzed online by chromatograph HP 7890B.

[0052] In the present invention, the conversion rate of ethanol, the yield and selectivity of propylene are calculated based on the hydrocarbon group as 100%, that is, one molecule of ethanol is deducted from one molecule of "H 2 O'CH 2 " is used as the basis for calculation.

[0053] Example 1

[0054] Preparation of composite molecular sieves:

[0055] (1) According to the molar ratio of 10SiO 2 :3R:300H 2 O Molar composition: 416.7 g of ethyl orthosilicate, 353.4 g of tetraethylammonium hydroxide (25 wt %) and 815 g of water were mixed evenly and aged at 25° C. for 30 h to obtain a mixture I.

[0056] (2) 400 g of mixture I was crystallized at 90° C. for 96 h to obtain mixture II.

[0057] (3) Take 100 g of Al-Beta molecular sieve (silicon-aluminum molar ratio SiO 2 / Al 2 O 3 60), impregnated with 60 grams of aqueous solution containing 30 g of mixture II, aged at 25°C for 6 hours, dried at 100°C for 12 hours, and calcined at 550°C for 6 hours to obtain 102.8 g of precursor III.

[0058] (4) 257 g of mixture I and precursor III were mixed in a liquid-solid weight ratio of 2.5:1, and placed in a crystallization kettle for crystallization at 130°C for 48 hours. After washing with distilled water, drying at 120°C for 12 hours, and calcining at 550°C for 4 hours, an Al-Beta@Si-Beta composite molecular sieve was obtained, wherein the weight ratio of Si-Beta to Al-Beta was 1:10.

[0059] Preparation of catalyst:

[0060] The Al-Beta@Si-Beta tablets were crushed into 20-40 mesh particles, and the crushed Al-Beta@Si-Beta particles were taken and mixed with hexahydrate zinc nitrate containing 5 parts of ZnO, 2 parts of La 2 O3 of lanthanum nitrate hexahydrate, 3 parts of P 2 O 5 After impregnating 90 parts of composite molecular sieve Al-Beta@Si-Beta with an aqueous solution of phosphoric acid, the catalyst was aged at 25°C for 24 hours, dried at 120°C for 12 hours, and calcined at 550°C for 4 hours to obtain catalyst a.

[0061] 2 g of catalyst was reacted in a fixed bed microreactor at a reaction temperature of 500°C, an ethanol concentration of 20 wt%, and an ethanol weight feed space velocity of 1.5 h -1 The reaction data and the external surface activity of the catalyst are listed in Table 2.

[0062] Example 2

[0063] The preparation of the composite molecular sieve is the same as in Example 1.

[0064] Take 70 parts of Al-Beta@Si-Beta sample, mix with 20 parts of kaolin, crush into 20-40 mesh particles, and then add zinc nitrate containing 5 parts of ZnO, 2 parts of La 2 O 3 of lanthanum nitrate hexahydrate, 3 parts of P 2 O 5 The composite molecular sieve Al-Beta@Si-Beta was impregnated with an aqueous solution of phosphoric acid, aged at 25°C for 24 hours, dried at 120°C for 12 hours, and calcined at 550°C for 4 hours to obtain catalyst b. The evaluation conditions of the catalyst were the same as those in Example 1.

[0065] Example 3

[0066] Preparation of composite molecular sieves:

[0067] (1) According to the molar ratio of 10SiO 2 :3R:300H 2 O molar composition: 416.7 g of ethyl orthosilicate, 353.4 g of tetraethylammonium hydroxide (25 wt %) and 815 g of water were mixed evenly and aged at 25° C. for 30 h to obtain a mixture I.

[0068] (2) Take 200 g of mixture I and crystallize it at 105° C. for 60 h to obtain mixture II.

[0069] (3) Take 100 g of Al-Beta molecular sieve (silicon-aluminum molar ratio SiO 2 / Al 2 O 3 40), impregnated with 60 grams of aqueous solution containing 30 grams of mixture II, aged at 25°C for 6 hours, dried at 100°C for 12 hours, and calcined at 550°C for 6 hours to obtain 102.8 grams of precursor III.

[0070] (4) 412 g of mixture I and precursor III were mixed in a liquid-solid weight ratio of 4.0:1, and then placed in a crystallization kettle for crystallization at 120°C for 72 h. After washing with distilled water, drying at 120°C for 12 h, and calcining at 600°C for 4 h, an Al-Beta@Si-Beta composite molecular sieve was obtained, wherein the weight ratio of Si-Beta to Al-Beta was 1.8:10.

[0071] The Al-Beta@Si-Beta tablets were crushed into 20-40 mesh particles, 98.5 parts of the crushed Al-Beta@Si-Beta particles were taken and mixed with 1 part of Ga 2 O 3 of gallium nitrate, 0.1 parts of CeO 2 Cerium nitrate, 0.4 parts P 2 O 5 The composite molecular sieve was impregnated with an aqueous solution of phosphoric acid, aged at 25° C. for 24 h, dried at 120° C. for 12 h, and calcined at 550° C. for 4 h to obtain catalyst C. The evaluation conditions of the catalyst were the same as those in Example 1.

[0072] Example 4

[0073] Preparation of composite molecular sieves:

[0074] (1) According to the molar ratio of 10SiO 2 :1.1R:1000H 2 O Molar composition: 416.7 g of ethyl orthosilicate, 129.6 g of tetraethylammonium hydroxide (25 wt%) and 3503 g of water were mixed uniformly at 25° C. and aged at 25° C. for 30 h to obtain a mixture I.

[0075] (2) Take 400 g of solution I and crystallize it at 90° C. for 96 h to obtain mixture II.

[0076] (3) Take 100 g of Al-Beta molecular sieve (silicon-aluminum molar ratio SiO 2 / Al 2 O 3 30), impregnated with 120g of mixture II, aged at 25°C for 10h, dried at 100°C for 12h, and calcined at 550°C for 6h to obtain 103.8g of precursor III.

[0077] (4) 1040 g of mixture I and precursor III were mixed in a liquid-solid weight ratio of 10:1, placed in a crystallization kettle and crystallized at 130°C for 48 h, washed with distilled water, dried at 120°C for 12 h and calcined at 550°C for 4 h to obtain an Al-Beta@Si-Beta composite molecular sieve, wherein the weight ratio of Si-Beta to Al-Beta was 2.8:10.

[0078] The Al-Beta@Si-Beta tablets were crushed into 20-40 mesh particles, 80 parts of the crushed Al-Beta@Si-Beta particles were taken and mixed with hexahydrate zinc nitrate containing 10 parts of ZnO, 10 parts of P 2 O 5 After being impregnated with an aqueous solution of phosphoric acid, the catalyst was aged at 25° C. for 24 h, dried at 120° C. for 12 h, and calcined at 550° C. for 4 h to obtain catalyst d. The catalyst evaluation conditions were the same as those in Example 1.

[0079] Comparative Example 1

[0080] The only difference compared with Example 1 is that Al-Beta is used in Comparative Example 1 to replace the composite molecular sieve in Example 1. The specific preparation method is as follows.

[0081] Al-Beta zeolite (silicon to aluminum molar ratio SiO 2 / Al 2 O 3 60) tablets were crushed into 20-40 mesh particles, and the crushed Al-Beta zeolite particles were mixed with 5 parts of ZnO hexahydrate zinc nitrate, 2 parts of La 2 O 3 of lanthanum nitrate hexahydrate, 3 parts of P 2 O 5 After impregnating 90 parts of Al-Beta molecular sieves with an aqueous solution of phosphoric acid, the catalyst was aged at 25° C. for 24 hours, dried at 120° C. for 12 hours, and calcined at 550° C. for 4 hours to obtain catalyst x. The catalyst evaluation conditions were the same as those in Example 1.

[0082] Comparative Example 2

[0083] The only difference compared with Example 1 is that Al-Beta@amorphous SiO 2 The composite molecular sieve in Example 1 is replaced, and the specific preparation method is as follows.

[0084] Al-Beta@Amorphous SiO 2 The preparation method is as follows: 100 g of Al-Beta zeolite (silicon-aluminum molar ratio SiO 2 / Al 2 O 3 60) containing 25 g of silica sol (40 wt% SiO 2 ) was impregnated with 70 g of aqueous solution, aged at 25 °C for 6 h, dried at 100 °C for 12 h, and calcined at 550 °C for 4 h to obtain SiO 2 @Al-Beta zeolite. Among them, SiO 2 The weight ratio with Al-Beta is 1:10.

[0085] SiO 2@Al-Beta zeolite tablets are crushed into 20-40 mesh particles, and the crushed SiO 2 @Al-Beta zeolite particles, with 5 parts of ZnO hexahydrate zinc nitrate, 2 parts of La 2 O 3 of lanthanum nitrate hexahydrate, 3 parts of P 2 O 5 90 parts of composite molecular sieve SiO 2 @Al-Beta, aged at 25°C for 24h, dried at 120°C for 12h and calcined at 550°C for 4h to obtain catalyst y. The catalyst evaluation conditions were the same as those in Example 1.

[0086] Comparative Example 3

[0087] The only difference compared with Example 1 is that 10 g of commercial Si-Beta zeolite and 100 g of Al-Beta zeolite synthesized in Example 1 are mixed evenly in a weight ratio of Si-Beta:Al-Beta=1:10 to obtain mechanically physically mixed zeolite HB.

[0088] The HB tablets were crushed into 20-40 mesh particles, 18 grams of crushed HB zeolite particles were taken, and zinc nitrate containing 5 parts of ZnO, 2 parts of La 2 O 3 of lanthanum nitrate hexahydrate, 3 parts of P 2 O 5 After impregnating 90 parts of HB with an aqueous solution of phosphoric acid, the catalyst was aged at 25°C for 24 hours, dried at 120°C for 12 hours, and calcined at 550°C for 4 hours to obtain catalyst z. The catalyst evaluation conditions were the same as those in Example 1.

[0089] Comparative Example 4

[0090] The only difference compared with Example 1 is that in Comparative Example 4, Si-Beta is used to replace the composite molecular sieve in Example 1.

[0091] The preparation method of Si-Beta is as follows: according to the molar ratio of 10SiO 2 :3R:300H 2 O molar composition: 416.7 g of ethyl orthosilicate, 353.4 g of tetraethylammonium hydroxide (25wt%) and 815 g of water were mixed evenly and aged at 25°C for 30 h to obtain mixture I. After mixture I was crystallized at 130°C for 30 h, it was washed with distilled water, dried at 130°C for 12 h and calcined at 550°C for 4 h to obtain Si-Beta zeolite.

[0092] The Si-Beta zeolite tablets were crushed into 20-40 mesh particles. The crushed Si-Beta zeolite particles were taken and mixed with hexahydrate zinc nitrate containing 5 parts of ZnO, 2 parts of La 2 O3 of lanthanum nitrate hexahydrate, 3 parts of P 2 O 5 After impregnating 90 parts of Si-Beta with an aqueous solution of phosphoric acid, the catalyst was aged at 25°C for 24 hours, dried at 120°C for 12 hours, and calcined at 550°C for 4 hours to obtain catalyst u. The catalyst evaluation conditions were the same as those in Example 1.

[0093] Table 1

[0094]

[0095] Table 2

[0096]

[0097] Table 3 Examples 1, 6 to 8 are the results obtained by using catalyst a to change the process conditions for 2h reaction

[0098]

[0099]

[0100] The above describes the specific implementation of the present invention in detail, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the various technical features being combined in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A catalyst for synthesizing biomass propylene, characterized in that: In parts by weight, the catalyst comprises: a) 1 to 20 parts of at least one oxide selected from Zn, In, Ga, W, and Mo; b) 0.5 to 10 parts of at least one selected from P and oxides of rare earth elements; c) 30 to 98.5 parts of Al-Beta@Si-Beta composite molecular sieve; d) 0 to 68 parts of matrix.

2. The catalyst according to claim 1, characterized in that The Al-Beta@Si-Beta composite molecular sieve in component c) is a core-shell composite molecular sieve with Al-Beta as the core phase and Si-Beta as the shell phase; the core-shell weight ratio is 70-99:1-30; More preferably, Si-Beta is an all-silicon Beta molecular sieve; Al-Beta is an aluminum-containing Beta molecular sieve, and the silicon-aluminum molar ratio SiO2 / Al2O3 is 10-400.

3. The catalyst according to claim 1, characterized in that The Al-Beta@Si-Beta composite molecular sieve has a specific surface area of ​​580 to 720 m 2 / g; and / or, an external surface activity index is less than or equal to 10%.

4. A method for preparing the catalyst according to any one of claims 1 to 3, comprising the steps of: The Al-Beta@Si-Beta composite molecular sieve is impregnated with an impregnation solution containing a source of component a), a source of component b) and optionally a source of component d), and then aged and calcined to obtain the catalyst.

5. The preparation method according to claim 4, characterized in that: The preparation method of the Al-Beta@Si-Beta composite molecular sieve comprises: 1) mixing a silicon source, a template R and water, and aging the mixture to obtain a mixture I; 2) taking a portion of the mixture I and subjecting it to hydrothermal crystallization to obtain a mixture II; 3) impregnating Al-Beta molecular sieve with an impregnation solution containing mixture II, and obtaining precursor III after aging and first calcination; 4) Another part of the mixture I is hydrothermally crystallized with the precursor III and then calcined for the second time to obtain the Al-Beta@Si-Beta composite molecular sieve.

6. The preparation method according to claim 5, characterized in that: In step 1), the feed ratio of silicon source, template R and water is SiO2:R:H2O=10:1-10:100-1000, in moles.

7. The preparation method according to claim 5, characterized in that: The silicon source in step 1) includes at least one of white carbon black, silica sol, silica gel and organic silicone grease; And / or, the template includes at least one of tetraethylammonium hydroxide and tetraethylammonium bromide.

8. The preparation method according to claim 5, characterized in that: The hydrothermal crystallization temperature in step 2) is 80-150° C., and the crystallization time is 24-196 hours.

9. The preparation method according to claim 5, characterized in that: In step 3), the temperature of the first calcination is 500-650° C. and the calcination time is 1-48 hours.

10. The preparation method according to claim 5, characterized in that: In the crystallization raw material of step 4), the liquid-to-solid ratio is 2:1 to 20:1 by weight.

11. The preparation method according to claim 5, characterized in that: The crystallization conditions of step 4) are: crystallization at 100-180° C. for 24-96 hours.

12. Use of the catalyst according to any one of claims 1 to 3 or the catalyst prepared by the preparation method according to any one of claims 4 to 11 in the reaction of preparing biomass propylene.

Citation Information

Patent Citations

  • Catalyst for preparing low carbon olefins by catalyzing bioethanol and preparation method and application of catalyst

    CN105148897A

  • Catalyst for catalyzing bioethanol to prepare low-carbon olefin and application of catalyst

    CN112958066A

  • Method for preparing arene and propylene from oxygen compound

    CN106608778A

  • Beta@Silicalite-1 type core-shell molecular sieve, and preparation method and application thereof

    CN109529922A

  • Method for preparing core-shell type Beta molecular sieve catalyst

    CN109701614A